The influence of interpersonal communication, work competence and work discipline on the performance of food and beverage msme employees through job satisfaction in Medan Johor District - Fajar Rezeki Ananda Lubis (Institute of Computer Science (IOCS), 2024)
This research aims to determine the influence of interpersonal communication, work competence, and work discipline on job satisfaction. This research involved 42 samples and used path analysis. The research results show that interpersonal communication has a positive effect on job satisfaction, while competence has a positive effect. Work discipline has a positive effect on job satisfaction, while interpersonal communication does not. Competence and work discipline do not have a significant effect on employee performance. However, job satisfaction has a significant effect on performance. The research results show that interpersonal communication, competence and work discipline have a positive but not significant effect on employee performance variables through the job satisfaction variable. Overall, this research highlights the importance of understanding these factors in improving job satisfaction and performance